1972
DOI: 10.1139/z72-076
|View full text |Cite
|
Sign up to set email alerts
|

Ducks nesting in association with gulls—an ecological trap?

Abstract: The reproductive success of ducks nesting in association with gulls on islands in Miquelon Lake, Alberta, was studied over a period of 3 years. Gulls protected nesting ducks by preventing other egg-eating birds from foraging on the islands. Pilfering of duck eggs by gulls was correlated with the point in incubation when ducks were trapped and handled. Without trapping, we estimated hatching success would exceed 90%. However, duckling mortality, concentrated in the 1st week posthatching, was positively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
150
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(151 citation statements)
references
References 14 publications
1
150
0
Order By: Relevance
“…The likelihood of a green turtle erroneously ingesting plastic debris, often by mistaking them for food, rose from 30% in 1985 to almost 50% in 2012 (Schuyler et al 2013). Human-induced rapid environmental change (HIREC, sensu Sih et al 2011) is filling animals' environments with new threats which bear little or excessive similarity to those they have encountered in their evolutionary history (Dwernychuk and Boag 1972;Patten and Kelley 2010;Witherington 1997). As a consequence, many of the stimuli involved fall outside the adaptive processing space of animals' evolutionary perceptual, learning, memory and decision-making systems, making individuals particularly vulnerable to their impact.…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood of a green turtle erroneously ingesting plastic debris, often by mistaking them for food, rose from 30% in 1985 to almost 50% in 2012 (Schuyler et al 2013). Human-induced rapid environmental change (HIREC, sensu Sih et al 2011) is filling animals' environments with new threats which bear little or excessive similarity to those they have encountered in their evolutionary history (Dwernychuk and Boag 1972;Patten and Kelley 2010;Witherington 1997). As a consequence, many of the stimuli involved fall outside the adaptive processing space of animals' evolutionary perceptual, learning, memory and decision-making systems, making individuals particularly vulnerable to their impact.…”
Section: Introductionmentioning
confidence: 99%
“…Although monitoring data collection is needed to confirm, this scenario is similar to the 'mega-trap' concept described by Kagan et al 15 , in which solar power developments act as an ecological trap as a result of the creation of favourable areas which offer reproductive and foraging advances within the surrounding ecosystem. 42 Exploring the impacts on fauna and habitat transformation in general combined with the feedback regarding the quality of biodiversity data sets used in the early stages of the EIA process justifies a clear concern, but it also creates a timeous opportunity. The timing in South Africa is ideal, considering that renewable energy developments are still in the early stages and there is a high potential to gain experience in these impacts.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…The ecological concept of a trap was proposed nearly half a century ago by Dwernychuk and Boag (1972), who suggested that this phenomenon may be common on the planet due to the considerable anthropogenic changes to the environment. One of the fundamental concepts is that an 'ecological trap' created by rapid anthropogenic change can facilitate extinction (Fletcher et al 2012).…”
Section: Introductionmentioning
confidence: 99%